A simple method of extracting Cap antigen of PCV2b from emulsified vaccines for testing its stability and antigenicity. (March 2017) - Yu, Cheng; Li, Xin; Diao, Wenzhen; Liu, Jiwei; Yao, Yunpeng; Hua, Li; Yu, Yaqin; Yu, Yongli; Wang, Liying
Abstract: Oil-based emulsions are commonly used adjuvants for veterinary vaccines. After formulation, it is required to extract protein antigens from emulsified vaccines for testing their stability and antigenicity. To establish a simple method to extract the protein antigens, two emulsified vaccines, designated as Cap-206 and Cap-35, were prepared by formulating a 28-kDa capsid protein (Cap) of PCV2b with ISA 206, a water-in-oil-in-water emulsion, or ISA 35, an oil-in-water emulsion. We found that the freeze-thaw-centrifugation method with steps of freezing at −20 °C for 12 h, thawing at room temperature and centrifuging at 9000× g for 10 min could separate the aqueous phase from Cap-206, and a centrifugation method by centrifuging at 9000× g for 10 min could isolate the aqueous portion from Cap-35. The Cap proteins were recovered from the aqueous phase and could be evaluated for their stability and antigenicity by SDS-PAGE, Western blot and ELISA. The freeze-thaw-centrifugation or the centrifugation method could also be used to recover recombinant mycobacterial heat-shock protein 65, a larger protein with molecular weight of 57-kDa, from ISA 206 or ISA 35 emulsions. The methods could be used to recover protein antigens from oil-based emulsion formulated vaccines for monitoring their stability and antigenicity during vaccine manufacture and storage. Highlights: Generated recombinant PCV2b capsid protein antigens and formulated them in oil-based emulsions. Extracted the antigens from emulsions and showed their stability and antigenicity. Established a novel and simple extraction method for monitoring antigens formulated in emulsions.